A preliminary study of hydro-mechanical properties for bentonite-sand mixture. Issue 1 (1st January 2023) - Motoshima, T; Iso, S; Nishimura, T
Abstract: Radioactive waste is a consequence of treatment radioactive material in industrial, medical, military and research applications for remaining electrical energy. For high-level waste (HLW), spent fuel (SF) and long-lived waste categories, geological disposal at depths of much hundreds of maters is considered in safety design. This study has aim to appear that swelling pressures due to hydration effort, hydraulic conductivity and stress-strain properties associated to evaluation to stress paths using two different bentonite-sand mixture, which are Sodium type bentonite and Calcium type bentonite. These materials have key feature in hydro-mechanical properties established in many reported obtained from laboratory test and underground investigations. Swelling pressure test, hydraulic conductivity test and triaxial compression test are conducted out, and developed apparatus are useful to results for series of some testing programs. Particularly, salinity concentration with increasing and decreasing on considering salinity effort is so interesting that further changing is applied to hydraulic conductivity for bentonite. While large lateral pressures are applied the bentonite at triaxial compression test, depending on lateral pressure is obviously to strength parameters that are apparent cohesion and angle of internal friction.